2010
DOI: 10.15208/ati.2010.13
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations of submerged fermentation and synthesis of pectinolytic enzymes by Aspergillus Niger : Effect of inoculum size and age of spores

Abstract: The paper investigates effects of the different concentration of inoculums and age of spores in the synthesis of pectinolytic enzymes with the aim of their optimizing for maximal enzyme production and growth of the microorganism. The microorganism used in this work was the fungus Aspergillus niger MK-15, which was isolated from soil as a highly active producer of pectinolytic enzymes. The results showed that the concentration of the inoculum and age of spores have a pronounced effect on the pectinolytic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…(PSTF1) in submerged fermentation. Similar results were found with pectinase production by Aspergillus niger MK-15 in submerged fermentation, the optimal inoculum concentration was 3 % (3/100 ml) spores and optimal age of spores was 3 days old (Kiro 2010). This showed that the low inoculum size of Fusarium sp.…”
Section: Resultssupporting
confidence: 84%
“…(PSTF1) in submerged fermentation. Similar results were found with pectinase production by Aspergillus niger MK-15 in submerged fermentation, the optimal inoculum concentration was 3 % (3/100 ml) spores and optimal age of spores was 3 days old (Kiro 2010). This showed that the low inoculum size of Fusarium sp.…”
Section: Resultssupporting
confidence: 84%
“…Results show that inoculum density (final OD 600 ) has a pronounced effect on biosurfactant production. Observations are similar to those reported by Mojsov, Nath and Das and Ghosh . According to Stanbury et al the inoculum or seed culture density influences the duration of the lag phase, specific growth rate, biomass yield, sporulation and quality of the final product.…”
Section: Discussionmentioning
confidence: 99%
“…Dry stalk is usually stored in the form of hay or straw bales for the purpose of feeding animals and other uses. The wheat straw is also used for various purposes after fermentation (Mojsov, 2010, Singh et al, 2009) and pulp industry (Gübitz et al, 1998, Singh et al, 2009) for preparation of biochar (Goodall, 2010), medicine, and bioremediation (Dupont et al, 2006, Javed et al, 2012).…”
Section: Introductionmentioning
confidence: 99%